Haptic Revolver: Touch, Shear, Texture, and Shape Rendering on a Reconfigurable Virtual Reality Controller - Whitmire, Eric; Benko, Hrvoje; Holz, Christian; Ofek, Eyal; Sinclair, Mike (CHI 2018, 2018)
We present Haptic Revolver, also known as the Haptic Wheel, a handheld virtual reality controller that renders fingertip haptics when interacting with virtual surfaces. Haptic Revolver’s core haptic element is an actuated wheel that raises and lowers underneath the finger to render contact with a virtual surface. As the user’s finger moves along the surface of an object, the controller spins the wheel to render shear forces and motion under the fingertip. The wheel is interchangeable and can contain physical textures, shapes, edges, or active elements to provide different sensations to the user. Because the controller is spatially tracked, these physical features can be spatially registered with the geometry of the virtual environment and rendered on-demand. We evaluated Haptic Revolver in two studies to understand how wheel speed and direction impact perceived realism. We also report qualitative feedback from users who explored three application scenarios with our controller.
Honorable Mention